Uma abordagem baseada em ontologias para integração semântica de ferramentas de apoio à medição de software - Fonseca, Vinícius Soares (2015)
Software measurement is considered a fundamental practice to support process improvement and project management, since it provides useful data for decision making at organizational and project levels. In order to be effective, software measurement must be guided by organizational or project goals, otherwise measures can be defined and data can be collected without alignment with the actual organizational needs. Due to the nature of software measurement activities, the use of computational supporting tools is essential. However, considering that software measurement can be performed in the context of various software processes and these processes generally have different supporting tools, it is common to use several tools to allow collecting data regarding the processes. Tools are usually developed at different time, by different teams and without concern for integration. As a result, organizations have to deal with integration issues to enable the communication between tools and properly support the measurement process. A key factor for integration is the sharing of a common understanding between the tools regarding the meaning of the exchanged terms and services. In other words, it is important to deal with integration not only in the syntactic level, but also in the semantic level. Among the instruments used to address semantics, ontologies have been acknowledged as an important means to address tool semantic integration. They can be used as an interlingua to map concepts and services used by the different applications. Considering this scenario, this work explores the use of measurement domain and task ontologies for tool integration aiming to support the software measurement process. For that, OBA-SI (Ontology-Based Approach for Semantic Integration) (CALHAU, 2011) is specialized to help integration of software measurement supporting tools by using a goal-based approach for requirements elicitation. To evaluate the proposal, the approach was applied to integrate tools aiming to support the measurement process in an actual software development organization.